The Relationship Between Export And Economic Growth In Turkey - Ucan, Okyay; Akyildiz, Abdulmenaf; Maimaitiaili, Maimaitimansuer (European Scientific Journal, ESJ, 2016)
Turkish economy has joined globalization after the year 1980 by abandoning the imported substitution growth strategy and adopting an economic growth strategy towards exportation. In this paper, the relationship between export and growth will be handled through a theoretic and Turkish economy framework. Then the existence of a relationship between export and growth in the Turkish economy will be shown through a cointegration analysis and Granger causality test using quarterly data between years 2006- 2015. It is found that, in the relationship between export and growth, there is a unidirectional causality from total export towards growth and no causality relation is found between total import and economic growth.